Scale‐Up Synthesis of High Purity Calcium Terephthalate from Polyethylene Terephthalate Waste: Purification, Characterization, and Quantification. Issue 12 (13th October 2021) - Li, Yanyan; Yi, Hongling; Ge, Mingqiao; Yao, Donggang
Abstract: The large‐scale synthesis of calcium terephthalate (CaTP) and upcycling of poly(ethylene terephthalate) (PET) are performed simultaneously by reactive processing. In the one‐pot synthesis, a spindle‐like calcium trihydrate CaTP‐80 with good crystallinity is derived and separated from PET waste by calcium hydroxide and water. Characterization techniques including Fourier‐transform infrared spectroscopy (FTIR), NMR, X‐ray diffraction (XRD), and thermal gravimetric analysis (TGA) reveal that the produced CaTP‐80 with an average size of 18.8 µm is tunable in the structure after calcination. The resulting anhydrous CaTP‐350 with different bonding modes between Ca 2+ and COO − exhibits high purity and thermal stability. Furthermore, an accurate quantification method operated by UV–vis is applied to define the selectivity and yield of CaTP powder from the complex intermediates. The effects of temperature, time, and concentration parameters on the yield of CaTP in the purification process are investigated. Results reveal that the optimum conditions are achieved with 88.2% conversion of PET to CaTP, 95.9% selectivity, and 84.6% yield of the synthesized CaTP‐350. The study complements the purification, characterization, and quantification of PET‐derived CaTP powder, which exhibits a model for effective and sustainable upcycling of PET waste. Abstract : The paper develops a sustainable method to upcycle poly(ethylene terephthalate) (PET) waste into high‐purity value‐added calcium terephthalate (CaTP). The transformation is quantitated by UV–vis results and optimized for higher PET conversion (88.2%) and CaTP selectivity (95.9%). The PET‐derived CaTP with tunable structure exhibits good crystallinity and high thermal stability, suggesting a model for green upcycling of PET wastes.